Long way home; The life history of Chinese-Indonesian migrants in the Netherlands - Kitamura, Yumi (Wacana, Journal of the Humanities of Indonesia, 2017)
The purpose of this paper is to trace the modern history of Indonesia through the experience of two Chinese Indonesians who migrated to the Netherlands at different periods of time. These life stories represent both post-colonial experiences and the Cold War politics in Indonesia. The migration of Chinese Indonesians since the beginning of the twentieth century has had long history, however, most of the previous literature has focused on the experiences of the "Peranakan" group who are not representative of various other groups of Chinese Indonesian migrants who have had different experiences in making their journey to the Netherlands. This paper will present two stories as a parallel to the more commonly known narratives of the "Peranakan" experience.